Reconciliation of Human Rights, Positive Law, and Siyasah Syar'iyyah: An Innovative Approach to Addressing Human Rights Issues in the Contemporary Era - Muannif Ridwan; Usman Jayadi; Sobardo Hamonangan; Daniel Tanati; James Yoseph Palenewen (MILRev: Metro Islamic Law Review, 2025)
This study explores the reconciliation of Human Rights, positive law, and siyasah syar‘iyyah as an innovative approach to addressing contemporary human rights challenges. The tension between the universal norms of human rights and Islamic law often becomes a focal point in global discourse, particularly in countries with Muslim-majority populations. Using a qualitative-descriptive approach and normative analysis, this research examines the convergence and potential integration points among these three pillars. The goal is to develop a legal framework that is more holistic, just, and contextually grounded. The findings reveal that through epistemological dialogue and the contextual reinterpretation of religious texts, siyasah syar‘iyyah can bridge the principles of Sharia and modern human rights values. Meanwhile, positive law—as a state instrument—can accommodate transcendent values of justice, provided it is formulated with sensitivity to society's social, cultural, and religious dynamics. This study recommends an inclusive legislative model and a humanistic approach to interpreting religious texts to strengthen legal legitimacy and the protection of human rights. The academic contribution of this research lies in developing an integrative approach that systematically unites three bodies of knowledge: human rights theory, modern legal theory, and the thought of siyasah syar‘iyyah. The conceptual framework is a normative and practical model for inclusive and just legal policymaking.